2007
DOI: 10.1136/jech.2005.038505
|View full text |Cite
|
Sign up to set email alerts
|

Validity of an adaptation of the Framingham cardiovascular risk function: the VERIFICA study

Abstract: The Framingham function adapted to local population characteristics accurately and reliably predicted the 5-year CHD risk for patients aged 35-74 years, in contrast with the original function, which consistently overestimated the actual risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
100
2
34

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 271 publications
(137 citation statements)
references
References 30 publications
1
100
2
34
Order By: Relevance
“…The consumption of other substances (hashish, alcohol, cocaine, heroin and methadone) was provided by the patient. The Regicor scale [12] (Framingham scale adapted to the Spanish population) was used to identify CV risk. In phase 2, pharmacological treatment was assessed and the use of bupropion, varenicline and/or NRT was considered.…”
Section: Methodsmentioning
confidence: 99%
“…The consumption of other substances (hashish, alcohol, cocaine, heroin and methadone) was provided by the patient. The Regicor scale [12] (Framingham scale adapted to the Spanish population) was used to identify CV risk. In phase 2, pharmacological treatment was assessed and the use of bupropion, varenicline and/or NRT was considered.…”
Section: Methodsmentioning
confidence: 99%
“…REGICOR is the Framingham model calibrated for the Spanish population (7)(8)(9). To calculate this scale of cardiovascular risk data on age, sex, tobacco consumption, systolic and diastolic blood pressure, cholesterol, HDL cholesterol, and diabetes are needed.…”
Section: Measurements and Calculationsmentioning
confidence: 99%
“…42,43,44 Moreover, the differences between observed and expected risk levels could be significant within some risk percentiles, 45 especially when unvalidated local risk estimation systems are used. 46,47,48 For example, the differences on the expected average risk for a sample of Koreans subjects using the Framingham score (7.65%) and the "local" Korea score (1.67%) is substantial. 48 Recalibration of the Framingham score for the Spanish population showed that the levels of absolute total CVR should be different in Spain.…”
mentioning
confidence: 99%
“…48 Recalibration of the Framingham score for the Spanish population showed that the levels of absolute total CVR should be different in Spain. 47 The predictive value of the risk models is affected by the presence of factors that are usually not included in the CVR models, such as low physical activity, obesity, being of low socioeconomic status and other psychological factors, pre-DM, a family history of premature CVD, or increased triglycerides, fibrinogen, apolipoprotein B, lipoprotein(a) levels and high-sensitivity Creactive protein. 9 In addition, it is important to point out that there are no validated tables for most low and middle income countries, where over three quarters of deaths from CVD occur.…”
mentioning
confidence: 99%